Impact of age at diagnosis on disease progression in patients with primary sclerosing cholangitis. Issue 2 (March 2018) - Rupp, Christian; Rössler, Alexander; Zhou, Taotao; Rauber, Conrad; Friedrich, Kilian; Wannhoff, Andreas; Weiss, Karl-Heinz; Sauer, Peter; Schirmacher, Peter; Süsal, Caner; Stremmel, Wolfgang; Gotthardt, Daniel N
Background: The median age of diagnosis of primary sclerosing cholangitis (PSC) is ∼30–40 years. Objective: We aimed to analyse disease progression and liver-dependent survival in patients diagnosed with PSC after 50 years of age. Methods: Patients with PSC were analysed with regard to their age at diagnosis. Patients with a first diagnosis of PSC after the age of 50 years were considered as the late-onset group. Results: A total of 32/215 (14.9%) patients were diagnosed with PSC after 50 years of age. The proportion of females was significantly higher among patients with late-onset PSC (48.4 vs. 27.3%; p  = 0.02). Patients with later diagnosis required dilatation therapy more often due to dominant stenosis (84.2 vs. 53.1%; p  = 0.01) and suffered from recurrent cholangitis more often (48.3 vs. 21.0%; p  = 0.003). Patients with late-onset PSC had reduced transplantation-free survival (10.5 ± 0.6 years vs. 20.8 ± 1.7 years, p  < 0.0001), with progredient liver failure and cholangiocarcinoma as the leading causes of death. Conclusions: Patients with later age at diagnosis of PSC displayed a different clinical phenotype with a different sex ratio, immune status and an increased risk for progressive liver failure and biliary malignancies.